Antioxidant activity and identification of flavonoid compounds in Patat leaves (Phrynium capitatum) ethyl acetate extract - Ahmad Fathoni; Alhady Nareswara Candraditya; Tarso Rudiana (Pascasarjana Universitas Negeri Medan, 2022)
Flavonoids are the biggest compound from the phenolic group that has the function of antioxidants. One of the plants with flavonoids is patat (Phrynium capitatum), which is usually used as food wrapping material. This study aims to quantify total flavonoid content, antioxidant activity and identify flavonoids from patat leaves ethyl acetate extract. Patat leaves sample cleaned, dried, and grinded. Grinded patat leaves were macerated gradually for 2 × 24 hours with n-hexane, ethyl acetate, and methanol solvent. The extract undergoing total flavonoids test guided with AlCl3 and CH3COONa. Extract with the biggest flavonoids content proceed to antioxidant activity test by SOD (superoxide dismutase) method and analyzed for the flavonoid structure by UHPLC MS/MS (ORBITRAP HRMS). The biggest total flavonoids are ethyl acetate extract with 8.678 mg QE/g; then methanol extract with 5.296 mg QE/g; and n-hexane extract was not tested because of negative results in the qualitative test. The antioxidant activity of the ethyl acetate extract of patat leaves is classified as inactive, with an Ic50 value of 488.299 ppm. The low antioxidant activity is due to the sample, which is still a matrix containing many compounds. The flavonoid compounds identified by its fragmentation pattern were kaempferide, formononetin, and pinostrobin.Keywords: Antioxidant; Flavonoids; Patat; Total flavonoids; UHPLC MS/MS